Mustahik Implementation Fȋsatȋlillȃhin Distribution Of Zakat Funds Maq Perspectiveṣid Al-Syarȋʽah (Study At Amil Zakat Institution In Bandar Lampung City) - Azis, M. Abdul; Ghozali, Abdul Malik; Habibi, Ahmad (ASAS, 2023)
This study aims to find out how the implementation of mustahik fȋ sabȋlillȃh in the distribution of zakat funds at the Amil Zakat Institution (LAZ) in Bandar Lampung City, which will then be analyzed using the theory of maqâṣid al-syarȋʽah and maṣlaḥah as analytical tools. This study uses qualitative methods with primary, secondary and tertiary data. Data analysis techniques in this study used qualitative data analysis techniques. The results of this study can be explained that the implementation of mustahik fȋ sabȋlillȃh in distributing zakat funds at the Amil Zakat Institution (LAZ) of Bandar Lampung City, it can be explained that all forms of programs for the collection, utilization and distribution of zakat in Indonesia refer to the regulations that govern, namely the Law No. 23 of 2011 concerning Management of Zakat and Regulation of the National Zakat Agency (BAZNAS) No. 3 of 2018 concerning the Distribution and Utilization of Zakat. In the utilization of zakat funds for productive activities there are several procedures, these rules are contained in Law No. 23 of 2011 concerning Zakat Management, CHAPTER V Article 29, The fȋ sabȋlillȃh group is a group that gets more attention than other groups. This is due to the expansion of meaning in interpreting and understanding the implementation of fȋ sabȋlillȃh. And the review of maqaṣid al-syarîʽah on the implementation of mustahik fȋ sabȋlillȃh in the distribution of zakat funds at the Amil Zakat Institution (LAZ) of Bandar Lampung City can be seen that when viewed from the formulation of maqaṣid al-Syarîʽah this is associated with the distribution of zakat to asnaf fȋ sabîlillâh, then the distribution is therefore, most of the problems lead to ḥifẓ al-dîn, to protect religion, and ḥifẓ al-‘aql, to protect reason.Keywords: BAZNAS, distribusi, fȋ sabȋlillȃh, maqaṣid al-Syarîʽah